Dynamika procesu organizacyjnego uczenia się jako element oceny efektywności zarządzania kapitałem intelektualnym - Sokołowska, Agnieszka (Dynamic of Organizational Learning Process as Element of Valuation of Intellectual Capital Management Effectiveness, 2006)
The article emphasises importance of organizational learning process in dynamic aspect as pivotal determinant intellectual effectiveness, identifies elements of intellectual capital management and describes categories: intellectual effectiveness, organisational learning process dynamic.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 184-195